Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbasis Outdoor Study terhadap Kemampuan Menulis Karya Ilmiah dan Hasil Belajar Geografi Siswa - Hamrin Hamrin; Budijanto Budijanto; Didik Taryana (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This research aims to describe the influence of outdoor study-based guided inquiry on students' skills in compiling scientific papers and learning outcomes of geography. Using a quasi-experimental design, consisting of two classes, namely the IPS2 class (experiment) and IPS1 (control). The research subjects of class XI IPS at SMAN 1 Mawasangka Timur in the academic year 2020/2021. Selection of classes using purposive sampling technique. Data analysis using MANOVA. The results showed the sig. The Manova test is 0.000 < 0.05 for the ability to write geography scientific papers and 0.001 < 0.05 for learning outcomes, meaning that there is an influence of an outdoor study-based guided inquiry model on the skills of compiling scientific papers and student learning outcomes.Abstrak: Penelitian ini bertujuan menguraikan pengaruh inkuiri terbimbing berbasis outdoor study pada keterampilan menyusun karya ilmiah dan hasil belajar geografi siswa. Menggunakan desain eksperimen semu, terdiri dua kelas, yakni kelas IPS2 (eksperimen) dan IPS1 (kontrol). Subjek penelitian siswa kelas XI IPS SMAN 1 Mawasangka Timur tahun pelajaran 2020/2021. Pemilihan kelas dengan teknik Purposive sampling. Analisis data menggunakan MANOVA. Hasil penelitian menunjukan nilai sig. uji Manova sebesar 0,000 < 0,05 untuk kemampuan menulis karya ilmiah geografi dan 0,001 < 0,05 untuk hasil belajar, artinya teradapat pengaruh model inkuiri terbimbing berbasis outdoor study pada keterampilan menyusun karya ilmiah dan hasil belajar geografi siswa.